2022
DOI: 10.3389/fneur.2022.781240
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Characteristic Analysis of Aneurysm Wall Enhancement in Unruptured Middle Cerebral Artery Aneurysm

Abstract: Background and PurposeAneurysm wall enhancement (AWE) on vessel wall magnetic resonance imaging has been suggested as a marker of the unstable status of intracranial aneurysm (IA) and may predict IA rupture risk. However, the role of abnormal hemodynamics in unruptured IAs with AWE remains poorly understood. This study aimed to determine the association between abnormal hemodynamics and AWE in unruptured middle cerebral artery (MCA) aneurysms.MethodsA total of 28 patients with 32 bifurcation aneurysms of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As mentioned earlier, low WSS may promote inflammatory cell infiltration, leading to pathological changes in the aneurysm wall. At the same time, increased vascular permeability may facilitate the penetration of contrast media into the aneurysm wall ( Zhong et al, 2022 ). Therefore, the enhanced regions showed the characteristics of low WSS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned earlier, low WSS may promote inflammatory cell infiltration, leading to pathological changes in the aneurysm wall. At the same time, increased vascular permeability may facilitate the penetration of contrast media into the aneurysm wall ( Zhong et al, 2022 ). Therefore, the enhanced regions showed the characteristics of low WSS.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between AWE and other hemodynamic parameters such as RRT, GON, and OSI is still controversial. It has been reported that circumferential wall enhancement is associated with long RRT ( Lv et al, 2020 ; Zhong et al, 2022 ). RRT, as an index of low or oscillatory WSS, reflects the residence time of blood near the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations